2019
DOI: 10.1177/0959683619887417
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphy and radiocarbon ages of late-Holocene Las Derrumbadas rhyolitic domes and surrounding vents in the Serdán-Oriental basin (Mexico): Implications for archeology, biology, and hazard assessment

Abstract: The Serdán-Oriental lacustrine basin in the eastern part of the Trans-Mexican Volcanic Belt holds a volcanic field of >30 monogenetic vents. Among them, the ~1000-m-high, ~11 km3 Las Derrumbadas rhyolite twin domes dominate the interior of the basin and are surrounded by smaller scoria cones, lava flows, shields, tuff rings, and maars. Of interest in this area are rare endemic species encountered in some of the maar lakes, as well as the large number of pre-Hispanic archeological sites indicating that the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 93 publications
1
5
0
1
Order By: Relevance
“…The central and southern Mexico region is a particularly interesting case of study as monogenetic fields are large and numerous in this area and display significant diversity with respect to their size, chemical composition, prevalent volcano type, and association or not with a central volcano (e.g., Guilbaud et al 2009;Chédeville et al 2020;Sieron et al 2021). To assess more quantitatively the variety that exists in this region and identify the controlling factors, we chose to focus on two relatively well-studied fields that contain preserved scoria cones of similar age (Late Pleistocene to Holocene, mainly) but are located in widely separated sectors of the volcanic arc: The Sierra Chichinautzin volcanic Field in the central-eastern sector of the Trans-Mexican Volcanic Belt and the Los Tuxtlas Volcanic Field situated to the SE of the belt (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The central and southern Mexico region is a particularly interesting case of study as monogenetic fields are large and numerous in this area and display significant diversity with respect to their size, chemical composition, prevalent volcano type, and association or not with a central volcano (e.g., Guilbaud et al 2009;Chédeville et al 2020;Sieron et al 2021). To assess more quantitatively the variety that exists in this region and identify the controlling factors, we chose to focus on two relatively well-studied fields that contain preserved scoria cones of similar age (Late Pleistocene to Holocene, mainly) but are located in widely separated sectors of the volcanic arc: The Sierra Chichinautzin volcanic Field in the central-eastern sector of the Trans-Mexican Volcanic Belt and the Los Tuxtlas Volcanic Field situated to the SE of the belt (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The maar volcanoes record periodic fluctuations in the water-magma interactions, resulting in diverse sizes and shapes of their craters. Some depict ellipsoidal-shaped forms with aligned scoria and spatter cones, such as Aljojuca ( 14 C: 4.1 ± 0.03-2.8 ± 0.03 ka, De León-Barragán et al, 2020, p. 5.5 ka, Bhattacharya et al, 2015 2.6 ± 0.08 ka, Chédeville et al, 2020) (Figure 3b) and Tecuitlapa ( 14 C: 8.9 ± 0.13 ka, Chédeville et al, 2020) (Figure 2d), or show an irregular elongated shape such as Atexcac (Carrasco-Núñez et al, 2007) (Figure 3e), dated at 8.3 ± 0.9-5.1 ± 0.1 ka ( 14 C; Chédeville et al, 2020), Quechulac, La Preciosa, Xalapazco tuff cone (Abrams & Siebe, 1994), and others. These features indicate structurally-controlled phreatomagmatic conditions with temporal migration of the explosion locus (Ort & Carrasco-Núñez, 2009).…”
Section: Holocenementioning
confidence: 99%
“…The LTVF has an area of ~2,200 km 2 (Verma, 2006) and contains the highest number of PVs which account for 12.3% of the total of volcanic vents in this field. In the SOVF there are >30 monogenetic volcanoes (Chédeville et al, 2020) within an area of ~1530 km 2 with PVs representing 46.7% of the total volcanic vents. This is the highest population of PVs related to the volcanic vent population in a specific area within the TMVB.…”
Section: Location and Distributionmentioning
confidence: 99%
“…Applying adequate techniques for PV dating is crucial. The revision of the ages obtained for several PVs showed that Ar-Ar or K-Ar dating is not suitable for young structures, resulting in the need to date them again by the radiocarbon method (e.g., Sieron and Siebe, 2008;Chédeville et al, 2020).…”
Section: Age and Paleoclimatementioning
confidence: 99%
See 1 more Smart Citation